Upper cervical cord enterogenous cyst mimicking transient ischaemic attacks. (20th September 2013) - Marchionni, Marco; Tzerakis, Nikolaos; Tsang, Kai; Carey, Martyn
Abstract : A 76-year-old woman presenting with tetraparesis, left-sided hemisensory loss and occasional neck pain was urgently admitted to our department. A cervical spine MRI scan revealed a partially cystic lesion compressing the cord at the C2–4 level. The lesion was surgically excised. The histopathological diagnosis was that of an enterogenous cyst. No postoperative complications were noted and the patient significantly recovered from the preoperative tetraparesis. Eleven months before surgery, a waxing and waning presentation of the myelopathic signs with normal neuroradiological findings on a non-contrast-enhanced head CT scan, had unfortunately led to the misdiagnosis of transient ischaemic attacks and ischaemic stroke which delayed the treatment of an essentially benign disease the total surgical excision of which not only is usually curative but also improves the preoperative signs and symptoms.